Adaptive Strategic Approaches and Their Impact on Economic Growth in Dynamic Markets - Goh, Thomas Sumarsan; Martinez, Samantha; Sitorus, Santa Lusianna; Anita, Tiurida Lily (Pandawan Sejahtera Indonesia, 2025)
In an era marked by accelerating globalization, digital disruption, and market volatility, businesses are compelled to develop adaptive strategic approaches to sustain performance and contribute to broader economic development. This study investigates how adaptive strategies characterized by flexibility, innovation, and responsiveness affect economic growth within dynamic market environments. The research aims to analyze the relationship between strategic adaptability and macroeconomic indicators such as GDP growth, productivity, and business resilience across varying national and industry contexts. Employing a mixed-method approach, the study integrates a systematic literature review with comparative case analyses from both developed and emerging economies, focusing on sectors experiencing rapid transformation. The findings reveal that organizations implementing adaptive strategies such as real-time decision-making, agile resource allocation, and continuous innovation are better positioned to respond to external shocks and, in turn, significantly enhance national economic performance. Moreover, the research highlights that countries with high levels of institutional support for strategic adaptability tend to achieve more sustainable growth trajectories. The study concludes that adaptive business strategies are not only essential for organizational competitiveness but also serve as key drivers of economic resilience in an increasingly uncertain global landscape. These insights offer valuable implications for policymakers, industry leaders, and researchers aiming to foster adaptive capacity as a means of achieving long-term economic stability and growth.